Quasar black hole masses and accretion rates across cosmic time. Issue Volume 15:Issue S359(2020) (March 2019) - Brotherton, Michael; Maithil, Jaya; Myers, Adam; Shemmer, Ohad; Matthews, Brandon; Dix, Cooper; Du, Pu; Wang, Jian-Min
Abstract: Quasar black hole masses are most commonly estimated using broad emission lines in single epoch spectra based on scaling relationships determined from reverberation mapping of small samples of low-redshift objects. Several effects have been identified requiring modifications to these scaling relationships, resulting in significant reductions of the black hole mass determinations at high redshift. Correcting these systematic biases is critical to understanding the relationships among black hole and host galaxy properties. We are completing a program using the Gemini North telescope, called the Gemini North Infrared Spectrograph (GNIRS) Distant Quasar Survey (DQS), that has produced rest-frame optical spectra of about 200 high-redshift quasars (z = 1.5–3.5). The GNIRS-DQS will produce new and improved ultraviolet-based black hole mass and accretion rate prescriptions, as well as new redshift prescriptions for velocity zero points of high-z quasars, necessary to measure feedback.